PERKEMBANGAN E-COMMERCE INDONESIA DALAM MENDORONG KEMAJUAN INDUSTRI KECIL MENENGAH (IKM) DI INDONESIA - Fandiyanto, Randika; Irawan, Bambang (Growth, 2025)
This study aims to analyze the development of electronic-based transactions or e-commerce in Indonesia from time to time. This research method is a qualitative descriptive study with an exploratory research approach. The development of e-commerce in Indonesia continues to experience significant development, this is driven by many factors such as the increasing number of Indonesian internet users, increasing digital literacy of the community, support for digital payments through fintech, encouragement of easy and fast delivery services, government regulations that provide easy access and full support and digital business trends in the future. The government has also provided regulations that have a significant impact on the development of digital transactions in Indonesia. The Benefits of E-Commerce for MSMEs include Expanding Market Reach, Increasing Sales, Ease of Marketing and Promotion, Operational Cost Efficiency, Ease of Business Management and Easier Transaction Recording